1984
DOI: 10.1099/00222615-17-3-259
|View full text |Cite
|
Sign up to set email alerts
|

The effect of capsular polysaccharide and lipopolysaccharide of Bacteroides fragilis on polymorph function and serum killing

Abstract: SUMMARY. The determinant responsible for the ability of Bacteroides spp. to inhibit polymorph phagocytic killing of aerobic organisms has not yet been identified. Therefore, the roles of lipopolysaccharide and capsular polysaccharide of B. fragilis were investigated. Serum-resistant and serum-sensitive strains of Proteus mirabilis were used to indicate inhibition of phagocytic killing and serum killing of aerobes. Whole organisms of B. fragilis, purified lipopolysaccharide and capsular polysaccharide were adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…The increased virulence of capsulate anaerobic bacteria and their synergic potential with other flora is believed to be mediated through increased resistance of these bacteria to phagocytosis and killing by polymorphonuclear leukocytes and macrophages (Ingham et al, 1977(Ingham et al, ,1981Namavar et al, 1983Namavar et al, , 1984Connolly et al, 1984). Furthermore, the capsulate bacteria have been shown to decrease phagocytosis of other organisms associated with them in mixed infections.…”
Section: Discussionmentioning
confidence: 99%
“…The increased virulence of capsulate anaerobic bacteria and their synergic potential with other flora is believed to be mediated through increased resistance of these bacteria to phagocytosis and killing by polymorphonuclear leukocytes and macrophages (Ingham et al, 1977(Ingham et al, ,1981Namavar et al, 1983Namavar et al, , 1984Connolly et al, 1984). Furthermore, the capsulate bacteria have been shown to decrease phagocytosis of other organisms associated with them in mixed infections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be important in virulence as capsular material can cause abscesses (Onderdonk et al, 1977) and capsules may be involved in adhesion (Onderdonk et al, 1978) and resistance to phagocytosis (Connolly et al, 1984;Lindberg & Weintraub, 1985). However, not all strains of B. fragilis are capsulate (Brook et al, 1984;Pruzzo et al, 1984) and cultures may contain capsulate and noncapsulate subpopulations (Babb & Cummins, 1978;Patrick & Reid, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…B. fragilis is often associated in mixed infections with aerobic bacteria and often seems to play a key role in their pathogenesis, since its elimination by prophylactic chemotherapy prevents the establishment of infection (Hofstad and Kristofferson, 1970;Gorbach and Bartlett, 1974). Recent work has shown that anaerobic bacteria inhibit the phagocytosis and killing of aerobic bacteria (Ingham et al, 1977;Jones and Gemmell, 1982;Namavar et al, 1983;Connolly et al, 1984;Vel et al, 1985). Much work has been done to determine possible virulence factors of B. fragilis.…”
Section: Introductionmentioning
confidence: 99%